À l’origine de tout, la Peur. Le cas de Roland Barthes - Marciniak, Magdalena (Romanica Silesiana)
In this paper I analyze several contexts in which the phenomenon of fear appears in Roland Barthes’ thinking In the first place, I will point out that Fear (written in capital letter in L’Image) placed “at the origin of everything”, becomes the fundamental fear, inseparable from the human condition. After all, for The Pleasure of the Text Barthes chose as its epigraph a quote by Thomas Hobbes ‘The only true passion in my life has been fear’, before introducing the idea of the proximity (identity?) of bliss and fear. Secondly, I will show that when Barthes writes about fear, he often refers to Donald Woods Winnicott’s article The Fear of Breakdown. In conclusion, I will point to an ambivalent status of fear in Barthes’s analysis: its recognition and acceptance are accompanied by desire for its disappearance. Key words: Roland Barthes, Fear, Donald Woods Winnicott